Multiple controlled random testing - V. A. Levantsevich; V. N. Yarmolik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Various methods for generating controlled random tests and their disadvantages are considered. Various numerical metrics are proposed and analyzed to construct multiple controlled random tests. The effectiveness of applying the Euclidean distance for the formation of multiple controlled random tests is substantiated and confirmed by experimental studies.